Analisis Biaya Kualitas, Tingkat persediaan Dan Turnover Karyawan PT Swarna Tangguh Cemerlang Terhadap Penjualan Dengan Profitabilitas Sebagai Variabel Intervening - Wibawa, Fauzi Satrya; Martono, Besar Agung (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
PT Swarna Tangguh Cemerlang faces problems with sales stagnation and declining annual profits. So the study aims to determine whether there is an effect of quality costs, inventory levels and employee turnover on sales with profitability as an intervening variable. The aim is to find a correlation between quality costs, inventory levels and employee turnover on sales with profitability as an intervening variable to determine the company's strategy. The method used is the Structural Equation Modeling (SEM) method using SmartPLS 3.0 PLS. The results of the direct relationship between variables are Quality costs (X1) Inventory levels (X2) have a positive and significant effect on Sales (Y) with T statistics of 26.525 and 2.158. Employee turnover (X3) has a significant negative effect on Sales (Y) with a T statistic of 2.048. The result is Quality costs (X1) have a significant positive effect on Profitability (Y) with T statistics of 4.912. Profitability (Z) has a positive and significant effect on Sales (Y) with T statistics of 20.468. Meanwhile, the intervening variable Quality Cost (X1) has a significant and positive influence on Sales (Y) with mediation from Profitability (Z) supported by a statistical T value of 5.143.